Determination of Uranium in Human Teeth, Bones and Tissues by the Fission Track Method - MORIWAKI, Kazunari; IKEDA, Nagao; SAIRENJI, Eiko; SASAKI, Emiko; NOGUCHI, Kunikazu (RADIOISOTOPES, 1977)
The uranium content of several human tooth, bone and soft tissue samples was determined by the fission track method. The average uranium content in teeth, bones and soft tissues were 6.7, 8.4 and 64 ppb ash, respectively. The distribution of uranium in bones is less uniform than that of teeth, and the uranium content of soft tissues is generally higher than that of teeth and bone. The presence of thorium does not interfere with the uranium determination in most cases.